The psychological experiences of using Islamic philosophy approach among women’s with advanced breast cancer in Indonesia - Komariah, Maria; Qadous, Shurouq Ghalib; Firdaus, Mohd Khairul Zul Hasymi; Agustina, Hana Rizmadewi; Mediawati, Ati Surya; Yulianita, Henny; Praptiwi, Atlastieka; Setyorin, Dyah; Permana, Ryan Hara (PKP Publishing Services Network, 2021)
BACKGROUND: Breast cancer turns a person’s life upside down, affecting every aspect of an individual including the psychological domain, such as feelings of phobia, isolation, anger, irritability, confusion, and most frequently anxiety. Some studies reported that rituals practice in Islam have an impact on the psychological health breast cancer patient. AIM: The aim of the study was to explore the experience of psychological alteration among patients with advanced breast cancer. METHODS: A qualitative study utilizing the content analysis approach was organized. Twenty Muslims with breast cancer during chemotherapy treatment with a mean age of 47.1 years who dealt with their psychological responses during treatment were invited to participate in a semi-structured interview, before and after applying Islamic-based practice therapy. This study conducted between February and June 2018 in the outpatient unit of chemotherapy in one of the Indonesia’s teaching hospitals. The generated data were transcribed verbatim and the content analysis approach was used for data reduction, data names, obtaining analytical code, and determining categories and themes. RESULTS: Four themes emerged from the data analysis before the researchers using the Islamic-based practice therapy: (1) Self-blaming, (2) feeling sad, (3) feeling fear and uncertain, and (4) living with a new body. However, the results after applying the Islamic-based practice therapy emerged three themes: (1) Closer to God, (2) peace of mind, and (3) inner strength. CONCLUSION: Overall, in the view of breast cancer patients, the psychological experience of using the Islamicbased practice therapy could change to positive responses by making them feel closer to God, having good inner strength, and a peaceful mind in dealing with their day-to-day conditions. Hence, understanding the patient’s experience will assist the nurses to promote professional abilities and improve nursing care delivery related to different cultural backgrounds and spiritual dimensions of Muslims patients.